LEARNING INDONESIAN LANGUAGE IN THE TIME OF THE COVID-19 PANDEMIC - Cecep Wahyu Hoerudin (GoAcademica Research dan Publishing, 2022)
During the Covid-19 pandemic, the learning process is carried out using established regulations. Through this regulation, the implementation of Indonesian language learning is carried out using Distance Learning. This study then tries to see how the implementation of Indonesian language learning occurs during the Covid-19 pandemic. This research will be carried out using a qualitative approach using previous studies and research data. The results of this study found that Indonesian language learning had not been implemented optimally during the pandemic. Then the understanding of teachers and other teachers is still lacking in the emergency curriculum. Finally, the achievement of learning outcomes during the pandemic found that students’ skills in writing texts were still lacking.